(untitled) (Journal of Informatics and Mathematical Sciences, 2012)
A two non-identical unit parallel system model is investigated and analysed. The system consists of two non-identical units, priority and non-priority arranged in parallel configuration. The priority unit is given preference in repair over non-priority unit. The priority unit is repairable but non-priority unit is not repairable and to be replaced after a random period of operation. The non-priority unit gives a signal for its replacement before going into failure mode and may be replaced by a new unit just after giving signal or upon failure. The failure and repair times of the priority unit are taken to be correlated random variables having bivariate exponential distribution. The failure time and the time after which non-priority unit gives signal are exponential random variables with different parameters and the time for replacement of non-priority unit is taken as general. The reliability analysis of this model has been carried out by using regenerative point technique.